THE EFFECT OF RETURN ON ASSETS, COMPANY GROWTH AND DEBT TO EQUITY RATIO ON COMPANY VALUE: PENGARUH RETURN ON ASSETS, COMPANY GROWTH DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN - Lilis Setyowati; Delta Claodya Sugiharto (Indonesian Journal of Economy, Business, Entrepreneurship and Finance, 2022)
The purpose of this study was to determine the effect of Return On Assets (ROA), Company Growth, and Debt to Equity Ratio (DER) on Company Value (study on manufacturing companies 2016-2020). The population in this study were manufacturing companies in 2016-2020 and the sample in this study was 46 companies. the sample with purposive sampling methode as many as 46 companies. The collected data were analyzed using multiple linear regression analysis test which was processed using SPSS. The results of the analysis show that Return On Assets (ROA) has an effect on firm value, company growth affects firm value, Debt to Equity Ratio (DER) has no effect on firm value